2010
DOI: 10.1007/s13238-010-0012-3
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of cytotoxin protein suilysin from Streptococcus suis

Abstract: Cholesterol-dependent cytolysins (CDC) are pore forming toxins. A prototype of the CDC family members is perfringolysin O (PFO), which directly binds to the cell membrane enriched in cholesterol, causing cell lysis. However, an exception of this general observation is intermedilysin (ILY) of Streptococcus intermedius, which requires human CD59 as a receptor in addition to cholesterol for its hemolytic activity. A possible explanation of this functional difference is the conformational variation between the C-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 34 publications
0
73
0
Order By: Relevance
“…Diffraction data from three-dimensional crystals of natively secreted LLO were used for structure determination by molecular replacement 30 with Perfringolysin O (PFO) 31 as a search model. Overall, the structure of LLO resembles that of the related CDCs PFO 31 , Anthrolysin O 32 , Intermedilysin 33 , Suilysin 34 and the recently published SLO 35 . LLO is an elongated, rod-like molecule with four distinct domains, referred to as D1 to D4 (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Diffraction data from three-dimensional crystals of natively secreted LLO were used for structure determination by molecular replacement 30 with Perfringolysin O (PFO) 31 as a search model. Overall, the structure of LLO resembles that of the related CDCs PFO 31 , Anthrolysin O 32 , Intermedilysin 33 , Suilysin 34 and the recently published SLO 35 . LLO is an elongated, rod-like molecule with four distinct domains, referred to as D1 to D4 (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Furthermore, the capsule interferes with the ability of S. suis to adhere to and invade host cells, since unencapsulated mutant strains showed a much higher adherence (and invasion) capacity when analyzed with different epithelial cell lines (12,13). Many virulent S. suis strains express a cholesterol-dependent pore-forming cytolysin, suilysin (14,15), which is the main bacterial factor causing host cell damage (13,16,17). It has been suggested that suilysin plays a role in the invasion of S. suis (13,16) as well as in immunomodulation and evasion of opsonophagocytosis (18)(19)(20), but its precise role in pathogenesis remains to be resolved.…”
mentioning
confidence: 99%
“…LLO is a unique CDC family member, as it is only active at low pH ranges (<5-6) but is inactive at neutral pH (7) or higher [71]. L. monocytogenes is internalized into host cells by phagocytosis or a bacterially activated internalization process.…”
Section: Dual-functional Tmhs In Llo From Listeria Monocytogenesmentioning
confidence: 99%
“…The crystal structures of six CDCs in the water-soluble monomer state have been solved, which revealed that CDCs also exhibit a high degree of tertiary structural similarity [2][3][4][5][6][7]. The homology between the primary and crystal structures of the CDCs predicts that CDC family members share many similar features and a common pore-forming mechanism, although it is clear there are some variations on this theme.…”
Section: Introduction To Cdc Familymentioning
confidence: 99%
See 1 more Smart Citation